Who Decides and Who Provides? The Anarchistic Housing Practices of John Turner as Realizations of Henri Lefebvre's Autogestive Space. (May 2016) - Bower, Richard
This article reframes the work of participatory development architect John Turner in the 1960s Peru as a practical realization of the political potential of autogestive space advocated in Henri Lefebvre's post-Marxist discourse. An analysis of the anarchistic politics that underpin Turner's participatory development reveals a critical intersection of autogestion and informal space and subsequently a questioning of the sociospatial resonances of anarchist practices and Marxist theories. This analysis is exemplified by the critical reframing of Lefebvre's much cited proposition of "The (Social) Production of (Social) Space" against Turner's anarchist questioning of "Who Decides and Who Provides?"